Preoperative Serum Thyroglobulin Levels Predict Radioiodine Therapy Outcome in Papillary Thyroid Microcarcinoma Patients - Cheng, Xian; Fan, Yijun; Ye, Wanzhong; Xu, Shichen; Wu, Jing; Gao, Wenjing; Bao, Jiandong; Yu, Huixin; Zhang, Li (Hormone and Metabolic Research, 2024)
Our previous study showed that elevated preoperative thyroglobulin (pre-Tg) level predicted the risk of developing radioiodine refractory in PTC patients. In the present study, we aimed to evaluate the prognostic value of pre-Tg in papillary thyroid microcarcinoma (PTMC). After a specific inclusion and exclusion criteria were applied, a total of 788 PTMCs were enrolled from Jiangyuan Hospital affiliated to Jiangsu Institute of Nuclear Medicine between Jan 2015 and Dec 2019. Among them, 107 PTMCs were treated with radioiodine therapy (RAIT) and the response to therapy was grouped as excellent response (ER), and non-excellent response (NER: indeterminate response, IDR and biochemical incomplete response, BIR). Multivariable logistic regression was used to identify predictors for the response of RAIT in PTMCs. Higher pre-Tg levels were detected in PTMCs with RAIT as compared with PTMCs without RAIT (p=0.0018). Higher levels of pre-Tg were also found in patients with repeated RAIT as compared with patients with single RAIT (p<0.0001). Furthermore, pre-Tg level was higher in PTMC with IDR (n=16) and much higher in BIR (n=9) as compared with patients with ER (n=82, p=0.0003) after RAIT. Multivariate analysis showed that pre-Tg level over 16.79 ng/ml [OR: 6.55 (2.10–20.39), p=0.001] was the only independent predictor for NER in PTMC with RAIT. We found that high level of pre-Tg predicted a poor RAIT outcome in PTMC. Our finding explores a prospective way in identifying high-risk PTMCs with poor response to RAIT.
Keywords: PTMC; preoperative thyroglobulin; radioiodine therapy; prognosis